PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL PADA KINERJA ALUMNI FAKULTAS EKONOMI UNIVERSITAS UDAYANA (Studi Empiris Mahasiswa MAKSI dan PPAk) - pande, putu mahardika pande mahardika (E-Jurnal Akuntansi; Vol 1 No 1 (2012), 2012)
This study aimed to determine the effect of intellectual, emotional intelligence and spiritual intelligence on the performance of graduates. Sampling study using purposive sampling method. Testing validity and reliability of the instruments used in the study had the validity and reliability were acceptable. Data analysis techniques using multiple linear regression. The results showed that intellectual intelligence and emotional intelligence affects the performance of the alumni, while spiritual intelligence has no effect on the performance of graduates
Keywords: id